Embryonic arrest at midgestation and disruption of Notch signaling produced by the absence of both epsin 1 and epsin 2 in mice - Hong Chen; Genevieve Ko; Alessandra Zatti; Giuseppina Di Giacomo; Lijuan Liu; Elisabetta Raiteri; Ezio Perucco; Chiara Collesi; Min Wang; Caroline J. Zeiss; Pietro De Camilli; Ottavio Cremona (2009)
Epsins are endocytic adaptors with putative functions in general aspects of clathrin-mediated endocytosis as well as in the internalization of specific membrane proteins. We have now tested the role of the ubiquitously expressed epsin genes, Epn1 and Epn2, by a genetic approach in mice. While either gene is dispensable for life, their combined inactivation results in embryonic lethality at E9.5-E10, i.e., at the beginning of organogenesis. Consistent with studies in Drosophila, where epsin endocytic function was linked to Notch activation, developmental defects observed in epsin 1/2 double knockout (DKO) embryos recapitulated those produced by a global impairment of Notch signaling. Accordingly, expression of Notch primary target genes was severely reduced in DKO embryos. However, housekeeping forms of clathrin-mediated endocytosis were not impaired in cells derived from these embryos. These findings support a role of epsin as a specialized endocytic adaptor, with a critical role in the activation of Notch signaling in mammals.